Drilling of CFRP-Ti6Al4V stacks using CO2-cryogenic cooling. (April 2021) - Rodríguez, A.; Calleja, A.; de Lacalle, L.N. López; Pereira, O.; Rubio-Mateos, A.; Rodríguez, G.
Highlights: Dry-drilling process for CFRP-Ti6Al4V aeronautical stacks was analyzed. CO2 cryogenic coolant was proposed and evaluated as an eco-friendly alternative. The use of cryogenics cooling improves dry drilling results. Abstract: In the work here presented, liquefied CO2 is used as cutting fluid for drilling CFRP-Ti6Al4V stacks as alternative to dry-drilling. Several tests were performed using dry-drilling technique, to compare this with the performance of CO2 cryogenic cooling. This work shows the feasibility of the proposed alternative, not only regarding technical issues but also environmental concerns. Results show that when CO2 is used in drilling, hole diameter values diverge below 0.5 % from nominal values, tool tip temperature is drastically reduced, and surface integrity of CFRP layers are preserved. Drilling tool edges damage is reduced and so tool life extended. In short, dry-drilling process was notably improved by CO2 assistance in comparison with dry drilling.